2020
DOI: 10.21203/rs.3.rs-68416/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Efficacy of Aromatherapy With Lemon Balm (Melissa Officinalis L.) on Sleep Quality in Cardiac Patients: A Randomized Controlled Trial

Abstract: Background: The importance of sleep in physical and mental well-being is generally acknowledged by both health professionals and the general public.This study investigated the effects on inhalation aromatherapy on sleep quality in cardiac patients.Methods: Ninety-six men and women aged between 20 and 75 were randomized to inhale aromatherapy essential oil from Lemon Balm (Melissa officinalis L.) or odorless sesame oil (the placebo) for 30 minutes twice daily for 3 days. Sleep quality by Verran Synder- Halpern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(42 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…Higgins et al (2019) stated that if participants are aware of their assigned intervention, it is more likely that health‐related behaviours will differ between the intervention groups 50 . Concerning deviations from intended interventions, four studies were rated as low risk 36‐38 and eight were rated as some concerns 39,41,57‐62 . Because most studies used a placebo or sham intervention in the control group, we answered no or no information about participants’ awareness of their assigned intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higgins et al (2019) stated that if participants are aware of their assigned intervention, it is more likely that health‐related behaviours will differ between the intervention groups 50 . Concerning deviations from intended interventions, four studies were rated as low risk 36‐38 and eight were rated as some concerns 39,41,57‐62 . Because most studies used a placebo or sham intervention in the control group, we answered no or no information about participants’ awareness of their assigned intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies [36][37][38][39][57][58][59][60][61][62] were conducted in Iran, and one study was performed in Turkey. 41 The studies were published between 2012 and 2020.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…41,42 In human randomized controlled trials (RCTs), lemon balm has demonstrated the ability to alleviate a series of neuropsychiatric symptoms, predominantly centered around depression and anxiety. Based on these trials, lemon balm interventions exerted the ability to reduce anxiety, depression, 43 insomnia, [44][45][46][47] postpartum depression, 48 anxiety induced palpitations, 49 anxiety in cardiovascular disease patients, 50 and healthy participants. 51 (Table 2) Akhoundzadeh et al, 52 inspired by the efficacy of lemon balm in treating amnesia, evaluated its effectiveness in Alzheimer's disease and cognitive disorders, revealing potential benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Lemon balm has been ingested across several centuries in various forms, which include direct food sources, decoction, or infusion. 53,54 Researchers have recently preferred to administer lemon balm interventions in the form of aqueous extracts, 10,50,51 hydroalcoholic extracts, 39,42 lyophilized aqueous extract, 49 essence, 45 or purified bioactive substances. 55,56 The recent evidence-based findings and lengthy history involving the application of lemon balm in neuropsychiatry, have provided vital knowledge in the field of mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Allocation concealment bias was specified as unclear in one study (Chehroudi et al, 2016) high risk in one study, (Lotfi et al, 2019) and low risk in the remaining 10 studies. Blinding of participants and personnel bias was determined as high risk in two studies (J.…”
Section: Methodological Quality and Risk Of Biasmentioning
confidence: 99%